Freshwater heritage : a history of sail on the Great Lakes, 1670-1918 - Bamford, Don (Natural Heritage Books, 2007)
Freshwater Heritage: A History of Sail on the Great Lakes, 1670-1918 represents the culmination of a lifelong passion for sailing and for the history of sail as it applies to Canada. Author/sailor/boat builder Don Bamford takes us deep into the psyche of sailing as it applies to historical events on the Great Lakes and to stories of the people and places there at the time. His extensive historical research takes us back to the time of European contact, through the fate of the luckless Griffon and the achievements of the French in the era of sail. From the 1760s through to 1815, Bamford chronicl.